Hate Speech and Hoaxes in Social Medias: The Dark Portrait of Uncertainty in Law Enforcement (Law Research Review Quarterly, 2021)
Social media is like a basic need for some people, the use of social media is very much, but the misuse of social media is often encountered, one of which is spreading hoaxes or hate speech through social media. This research is intended to analyze and examine hate speech and hoaxes spreading from the perspective of law enforcement as well as a legal instruments in Indonesia. This research emphasized and found that the prohibition of spreading hate speech itself is regulated in Article 28A of Law Number 11 of 2008 concerning Electronic Information and Transactions jo. Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. One of the recent cases that occurred was a high school teacher in Banten who spread hoax stories of hatred with the aim of reminding SMA 1 Sajiro Banten students to be aware of the latent dangers of communism that would emerge.